Demand Guarantees Under the OHADA Uniform Act on Securities - Enonchong, Nelson (Social Science Research Network, 2008)
This paper seeks to assess the extent to which the provisions of the Uniform Act dealing with demand guarantees meet the OHADA objective of modernisation to facilitate commercial activity. It notes that in general those provisions are to be welcomed as a helpful contribution towards the aforementioned OHADA objectives. However, it argues that there is scope for some improvement and that a revision of the provisions is desirable, primarily to give the parties greater commercial flexibility by allowing them more freedom of contract and to reduce the areas of uncertainty and confusion. It is proposed to consider the key benefits brought about by the Uniform Act before identifying and explaining the main areas of concern.
Keywords: Demand guarantees; OHADA Uniform Act on Securities

On formation of a share company in Ethiopia - Tesfay, Seyoum Yohannes (Journal of Ethiopian Law, 2008)
Keywords: Attributes; Ethiopian law; Formation; Share company

The Role of International Economic Law in Africa - Obale, Offah Ako (Society of International Economic Law (SIEL) Inaugural Conference 2008, 2008)
International Economic law (IEL) has a specific role to play in a complex modern Africa. The underdeveloped state of trade law regimes in Africa is arguably a reflection and product of the low level of commercial activity. The reverse is equally true in that underdevelopment in commercial activity on the continent is a reflection and product of the minimal role played thus far by international economic law.
Keywords: AEC; Africa; African; African Economic Community (AEC); Doha; Globilisation; International Economic Law; OHADA; Trade law; WTO

Recognition of various stakeholder interests in company management - Esser, Irene-Marié (University of South Africa, 2008)
Good corporate governance should be the cornerstone of all company management. Directors ought to know in whose interests the company should be managed. This thesis attempts to answer the following question: whose interests must be granted primacy in the management of a company? In chapter 1 it is stated that shareholders' interests are traditionally granted primacy in the management of a company. There has, however, been a shift in public opinion towards recognition of a wider variety of interests that should be considered than only those of the shareholders. These interests include, inter alia, environmental interests and those of the investors, employees and consumers. This thesis thus focuses on the primary stakeholders, namely individual shareholders, creditors, employees, consumers and suppliers. In chapter 2 a theoretical foundation is provided on the nature of a company. The different theories on the nature of a company, emphasising either shareholder primacy or stakeholder protection, are discussed. A combined new theory is proposed. It is suggested that the confusion relating to the meaning of "the company" needs to be eliminated. Chapters 3, 4 and 5 provide an international comparison of the company law in Botswana, Australia, New Zealand and the United Kingdom. The focus falls, firstly, on directors' duties, secondly, on the question in whose interests directors should manage a company and, thirdly, on the codification of their duties. In chapter 6 the South African position is evaluated. First, the possible stakeholders are identified and the protection currently afforded them is explained. The reports of the King Committee on Corporate Governance, the Policy Document on company law reform as well as the Companies Bill of 2007 are discussed. Draft clauses are recommended to be incorporated in new company legislation to provide directors with clarity on what is expected of them. It is the aim of this thesis to provide clarity on whose interests should receive primacy when directors manage a company. The outcome of this research should provide a clear indication to South African directors of what is expected of them and who the beneficiaries of their fiduciary duties are.
Keywords: Codes of best practice; Consumers; Corporate governance; Corporation law; Creditors; Directors' Duties; Shareholder value; Shareholders; Social responsibility of business; Stakeholders

Reforming Legal Reform in Francophone Africa: World Bank' Project Experience - Wabnitz, Hans-Werner (Islamic Law and Law of the Muslim World Paper, 2008)
You don't plant water lilies in the desert - The keystone of civilized society is justice. Without justice, neither peace nor development. A prerequisite is the populations' trust in legal institutions: the law and the courts. The alienation of the people with imposed legal institutions is the reason for Francophone Africa's lack of justice. To remedy the situation, this paper proposes to reconnect the people with the law through: (1) respecting local values in Village tribunals; (2) reforming lawmaking to comply with custom, accessible (also) in vernacular languages; (3) accessibility of law through the Internet. It is argued that the people, as client of justice, need to regain control over their law in order to respect it. Only then the necessary change of traditions and values is feasible. Women lawyer associations are identified as agents for such change. To redress modern courts, the paper suggests a concentration of tribunals, a tightening of procedure and rigorous control, in order to foster peer pressure for professionalism. The constitutional values are to serve as common bond.
Keywords: ACCESS TO JUSTICE; Africa; Colonial law; Corruption; Court administration; Culture; Customary law; Drafting; Equality; Fatwa; Gender; Honor; Human rights; Institutions; Justice; Law; Legal reform; OHADA; Paralegals; Participation; Reform; Tradition; Uniform Act; Village courts; Worldbank

Crossing the Wires: the Interface between Law and Accounting and the Discourse Theory Potential of Telecommunications Regulation - Carter, David Bernard (Victoria University of Wellington, 2008)
Regulating telecommunications is complex: international experience indicates that there is no 'successful' regulatory framework due to the balancing of industry and regulatory interests (Laffont & Tirole, 2000, p. 13). The New Zealand 'light-handed' regulatory experiment failed and the 1999 General Election presented an opportunity for change in telecommunications. The Labour-led Government in implementing a policy of 'responsible re-regulation' enacted the Telecommunications Act 2001, signalling the passage of "landmark telecommunications legislation ..." (Swain, 2001d). Within the Telecommunications Act 2001, 'cost' assumed a central regulatory role. It is this move to cost that this thesis considers in identifying, developing, and critiquing the interface of law and accounting. The thesis examines the increasing call for accounting information in law and regulation by interrogating the use, presentation, and reception of accounting to examine the interface between law and cost in the regulation of telecommunications. The Telecommunications Act 2001 incorporates total service long run incremental costing as the 'costing technique' for interconnection access and annual net costing for the Telecommunications Service Obligation. Through interrogating 'cost' as an accounting technology, in contrast to the economic and legal conception of cost as a simple, objective concept, the thesis illustrates the role of cost at methodological, technical, and political levels, and the challenges that this poses for telecommunications regulation. The thesis articulates the relevance of discourse theory to the interface of law and accounting. Consequently, the thesis investigates the formation and discursive enunciation of standpoints of political identities characterised by antagonism and uncertainty. This includes identifying attempts by interested parties, including industry actors, stakeholders, and the Government and its agents, to articulate 'new' discourses centred on nodal points around 'cost'. The rhetorical analysis examines how actors articulate the metaphorical element of 'cost' in agitating for particular costing methods to be included in the legislation. The empirical analysis examines the process of rhetorical condensation as arguments for and against the incorporation of total service long run incremental costing and net costing came to signify the complete failure of the light-handed regulation. Then, by examining the politics following the enactment of legislation, this condensation is unpacked. The analysis of the contestation over interpreting and implementing the regulation illustrates displacement of the 'common' signifier resulting in confusion and disappointment in relation to the aims of the new regulatory regime.

Some preliminary thoughts on a comparative law model for harmonisation of laws in Africa - Nicholson, Caroline (Fundamina : A Journal of Legal History, 2008)
This paper is premised upon acceptance of the view that some form of harmonisation of laws in Africa is a desirable objective and that comparative legal research is a tool that might effectively be applied in order to further the objective of harmonisation. That said, the time has come for comparatists in Africa to think afresh on the issues of globalisation and the need for harmonisation of laws in Africa, with a view to promoting peace, stability and scope for increased development in the region through greater regional economic co-operation.

United Nations Convention on Contratcts for the International Carriage of Goods wholly or partly by Sea (United Nations, 2008)
Keywords: Carriage of Goods; Contracts; International carriage; Rotterdam Rules; Sea

The development of performance requirements in international law and their effect on BITs and FTAs as well as on the agreeing parties - Bless, Christopher Josef Manfred (Universität Wien, 2008)
Performance requirements are part of a system of policy measures implemented by states to advance their economic, social and political objectives. A universally agreed upon definition of performance requirements is not available. Rather they are defined by the applicable legal norms and their assessment is dependent upon their effect on the parties of each individual case. The scope of legal protection these regulations provide must be measured separately for each norm within the scope of the specific legal framework. This dissertation has two objectives: First, the implementation and legal effect of performance requirements in international investment and trade law are investigated. Secondly, a legal test will be developed, that allows for an assessment of performance requirements. In a first step, the legal treatment of performance requirements will be analyzed from a theoretical perspective. Subsequently, the legal practices relating performance requirements and the relevant provisions in international investment and trade law will be identified. The developed legal test does not only do justice to the economic, social and political framework within which each performance requirement must be looked at but is also adaptable in a way that it can be applied to a variety of situations and legal traditions. It satisfies both the demands of legal certainty and clarity as well as facilitating the finding of justice on an individual basis. Understanding the advantages of foreign direct investment, the analysis performed aims promote the usage of performance requirements in a way that foreign direct investment will push the global economy forward.
Keywords: FIRA; Foreign direct investment; Free trade agreements; International Trade; International investment; Investment treaties; NAFTA; Performance requirements

The implications of the structure of the regulatory expropriation enquiry in international investment law - Bonnitcha, Jonathan Merrington (Oxford University, UK, 2008)
This thesis examines the structure of enquiry that arbitral tribunals use to distinguish between regulatory expropriation and legitimate non-compensable regulation in international investment law. The thesis proposes a new taxonomy of the possible structures of enquiry: the enquiry could look exclusively to the effects of the measure on the protected property; exclusively to the characteristics of the impugned measure; or to both the effects on the property and the characteristics of the measure. The application of this taxonomy shows that there is no agreed structure of enquiry in decisions on regulatory expropriation in international investment law. However, various threads of jurisprudence do show some degree of internal consistency. The thesis identifies six approaches in the decisions of arbitral tribunals: two that look exclusively to the effects of the measure; one that looks exclusively to the characteristics of the measure; and three that consider both the effects and the characteristics of the measure. Of the three approaches that consider both the effects and the characteristics of a measure, one is a direct adoption of US 5th Amendment jurisprudence and another is a direct adoption of ECHR Article 1 – Protocol 1 jurisprudence. Chapters 4 and 5 examine the jurisprudence of the US and ECHR in detail. These chapters show that, unlike international investment law, each of these jurisdictions has an established structure of enquiry in cases of regulatory expropriation. All six approaches to regulatory expropriation are sketched as models. These model approaches are applied to the case study of Piero Foresti. The case study demonstrates the most significant conclusion of this thesis: that different structures of enquiry, and different approaches within those structures, necessarily entail different legal outcomes on the same facts.
Keywords: 5th amendment; Bilateral Investment Treaties (BITs); Black economic empowerment; ECHR; Expropriation; Human rights; International Investment Law; MPRDA; Property law; Public international law; Regulatory expropriation; Right to property

Explaining Copyright: The Normative Implications of its Sociotechnical Construction - Nicholson, Scott (Queen’s University, 2008)
The construction of copyright law can be causally explained by two possible types of explanation: dialectical explanations and material explanations. I argue that an adequate causal description of the copyright discourses of Western legal systems must incorporate a material explanation in order to account for many of the general and particular characteristics of the evolution of copyright. As a vast variety of contingent and interactive social and technical conditions have caused the evolution of copyright, we should expect a plausible material explanation to be multifaceted and multi-layered. However, in addition to providing a causal sociohistorical description, a good legal explanation should also seek to include a normative account detailing the moral grounds of the law, or lack thereof. Dialectical explanations can be teleological: they can presuppose that the law is directed towards a perfect legal state and that it is essentially guided by a set of moral ideals. Material explanations, on the other hand, are essentially non-normative and do not explicitly address moral questions. But this does not entail the elimination of moral considerations from material explanations. As I aim to show, we should not address the moral and sociohistorical elements of copyright legal discourses independently because they are causally connected: moral justifications have been rhetorically used by social actors to influence lawmaking processes, and conversely, changes in technical conditions have given rise to sociotechnical formations that enable and structure the norms of copyright. Given this, I propose that lawmakers should adjudicate and legislate from a broad and flexible standpoint. They should not attempt to merely apply old principles to new problems, but should comprehend new moral norms introduced by new conditions, and balance them against the older, more established principles enshrined in traditional intellectual property theories.
Keywords: Copyright; Intellectual property

NEPAD and African Development: Towards a New Partnership between Development Actors in Africa - Tawfik, Rawia M. (African Journal of International Affairs, 2008)
The model required to drive socio-economic development in Africa, and the relationship between the state and the private sector based on that model, have sparked much controversy among African analysts. Some question the relevance of other successful models of development, such as in the liberal West or in East-Asia, to the African context. Others criticise all models of development that are “alien” to African cultures and conditions hence rejecting the NEPAD model on this basis. This paper argues that although NEPAD does not present a detailed model of the relationship between the state, the private sector and civil society in Africa, some of its theoretical underpinnings suggest a balanced framework that should prompt African scholars to search for new models that do not necessarily imitate already successful ones but respect the particularities of each African state